Bay lodyans : Haitian popular film culture - Accilien, Cécile, 1973- (SUNY series, Afro-Latinx futures., 2023)
"Considers how popular Haitian films not only provide entertainment but also help audiences in Haiti and the diaspora think through daily challenges"--